Four-step total synthesis of (+)-yaoshanenolides A and B - Thorat, Sagar S.; Palange, Megha N.; Kontham, Ravindar (ACS Omega, 2018)
A highly concise bioinspired four-step total synthesis of yaoshanenolides A and B possessing tricyclic spirolactone with an unusual 5'H-spiro-[bicyclo[2.2.2]-oct[2] ene-7,2'-furan]-5'-one scaffold is reported. This synthesis features high-yielding aldol-type addition of gamma-butyrolactone on to the aldehyde, exocyclic olefination of lactone derivative using Eschenmoser's salt, and highly facial-and endo-selective [4 + 2]-cycloaddition of fully functionalized 5-methylene-2(5H)-furanone with natural R-(-)-alpha-phellandrene. The approach allows access to yaoshanenolides A and B in four linear steps in 11 and 13% overall yield.

Fe(III)-Catalyzed diastereoselective friedel-crafts alkylation-hemiketalization-lactonization cascade for the synthesis of polycyclic bridged 2-chromanol lactones - Borade, Balasaheb R.; Nomula, Rajesh; Gonnade, Rajesh G.; Kontham, Ravindar (Organic Letters, 2019)
An unprecedented Fe(III)-catalyzed Friedel-rafts alkylation-hemiketalization-lactonization cascade of electron-rich hydroxy arenes and distinctively functionalized unsaturated 4-keto esters is developed for the construction of polycyclic bridged 2-chromanol lactones. Following this simple and facile protocol, a broad range of products was prepared in good to excellent yields as a single diastereomer. An unusual conglomerate (enantiomerically pure polymorph) of 3ac is reported along with the absolute stereochemistry, and the remaining products were rigorously confirmed by single-crystal X-ray analysis and analogy.

The first enantioselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C - Ingale, Sudhir R.; Vinodkumar, Ramavath; Kontham, Ravindar (Tetrahedron Letters, 2025)
Herein, we report the first stereoselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C using a chiral-pool strategy. This synthetic route features the use of readily available (S)-(+)-carvone as a chiral building block, Robinson annulation to construct the decalin system, substrate-controlled stereoselective methylation, single-step annulative construction of a tricyclic gamma-ylidene-butenolide with concomitant alkene transposition, and direct lactone-to-lactam conversion as key transformations.
Keywords: annulation reactions; Eremophilanes; Peniroqueforin C; Sesquiterpenoids; Total synthesis